A mutação constitucional proposta na reclamação N.4335/AC: a atribuição de efeito vinculante ao controle difuso de constitucionalidade na concretização dos direitos e garantias fundamentais - Nass, Anna Paula Masiero Rigo (2014)
An analysis is proposed of the new concept proposed in the Minister Gilmar Mendes and Minister Eros Grau, which aim to equate the effects of diffuse control with the concentrated control of constitutionality, without the participation of the Federal Senate, who, under the terms of Article 52, X1, of the Federal Constitution, is responsible give publicity to the suspension of the execution of law declared unconstitutional, incidentally, by final decision of the Federal Supreme Court. On the other hand, it is worth mentioning that the votes of the Ministers Sepúlveda Pertence (retired), Joaquim Barbosa and Ricardo Lewandowski are opposed to the argument of the equalization of effects, having been positioned by the literal maintenance of the provisions of Article 52, X, of the Federal Constitution . It is therefore questioned whether it would be possible to attribute erga omnes and binding effects to the decisions handed down in diffuse control, emanating from the Federal Supreme Court, through the constitutional change proposed in Complaint no. 4335 / AC, in the context of the Democratic State of Law.